The Role of the Polish Higher Education System in the Development of Entrepreneurship - Hanna Nowak (Entrepreneurial Business and Economics Review)
Objective: The objective of this paper is to present the perceived impact of entrepreneurship education in Poland from different perspectives (e.g. of national experts and students), especially at the tertiary school level, as well as discussing the role of the higher education system in entrepreneurial development.